Self-healing injectable multifunctional hydrogels for intervertebral disc disease - Zhengrong Gu; Yi He; Honglin Xiang; Qiwei Qin; Xinna Cao; Ke Jiang; Haoshaqiang Zhang; Yuling Li (Materials Today Bio)
Intervertebral disc degeneration (IVDD) is increasingly prevalent in aging societies and poses a significant health challenge. Due to the limited blood supply to the disc, oral medications and systemic treatments are often ineffective. Consequently, localized injection therapies, which deliver therapeutic agents directly to the degenerated disc, have emerged as more efficient. Self-healing injectable hydrogels are particularly promising due to their potential for minimally invasive delivery, precise implantation, and targeted drug release into hard-to-reach tissue sites, including those requiring prolonged healing. Their dynamic viscoelastic properties accurately replicate the mechanical environment of the natural nucleus pulposus, providing cells with an adaptive biomimetic microenvironment. This review will initially discuss the anatomy and pathophysiology of intervertebral discs, current treatments, and their limitations. Subsequently, we conduct bibliometric analysis to explore the research hotspots and trends in applying injectable hydrogel technology to treat IVDD. It will then explore the promising features of injectable hydrogels in biomedical applications such as drug, protein, cells and gene delivery, tissue engineering and regenerative medicine. We discuss the construction mechanisms of injectable hydrogels via physical interactions, chemical and biological crosslinkers, and discuss the selection of biomaterials and fabrication methods for developing novel hydrogels for IVD tissue engineering. The article concludes with future perspectives on the application of injectable hydrogels in this field.